Seguridad y hábitos alimentarios en preescolares de Trujillo antes y durante la pandemia por COVID-19 - Barrios Acosta, Hassler Danny (2022)
To determine if there is any variation in the food security and eating habits of preschoolers of the I.E 1682 "Virgen de Fátima" of Trujillo before and during the COVID-19 pandemic. Material and method: We selected 136 preschoolers in grades of 4 or 5 years old during the 2021 school year and applied electronic surveys regarding food security (FS) in their homes and their eating habits (EA) before and during the COVID-19 pandemic. The surveys were answered by parents or guardians. Results: There were statistically significant differences between the proportions of FS levels with respect to before and during the COVID-19 pandemic (p=0.000037), which evidenced a decrease in the level of FS with the pandemic. There was a decrease in the frequency of consumption of fruits (p=0.0411), red meat (p=0.0230), white meat (p=0.0320) and dairy products (0.0188), during the COVID-19 pandemic compared to before the pandemic, which was statistically significant. Conclusion: There is significant variation in the food safety and eating habits of preschoolers of the I.E 1682 "Virgen de Fátima" of Trujillo before and during the COVID-19 pandemic.